Effect of an IMCI intervention on quality of care across four districts in Cape Town, South Africa. Issue 4 (21st March 2005) - Chopra, M; Patel, S; Cloete, K; Sanders, D; Peterson, S
Abstract : Aims: To measure the change in quality of care provided to sick children as a result of the routine implementation of the IMCI intervention. Methods: Structured observations of consultations with sick children, exit interviews with caregivers, and facility reviews were conducted both before and after IMCI intervention in four health districts in Cape Town. Interventions were case management training, orientation courses for supervisors and medical officers, and some reorganisation of management systems. Results: Twenty one nurses in 21 clinics were observed before and after the IMCI intervention; 90 and 70 child observations were conducted before and after IMCI intervention respectively. There was a marked improvement in assessment of danger signs in sick children (7% before versus 72% after), assessment of co-morbidity (integrated score 5.2 versus 8.2), rational prescribing (62% versus 84%), and starting treatment in the clinic (40% versus 70%). However there was no change in the treatment of anaemia or the prescribing of vitamin A or counselling of caregivers. There was no change in the knowledge of caregivers regarding medication or when to return to the health facility. Facilities were well stocked and supervision regular both before and after IMCI. Conclusion: This study has shown that under normal operating conditions and in a context of good facility infrastructure and management support, IMCI is associated with improvements in some important aspects of care